Copper nanoparticles and reduced graphene oxide modified a glassy carbon electrode for the determination of glyphosate in water samples - Setznagl, Sarah [UNESP]; Cesarino, Ivana [UNESP] (Taylor & Francis, 2020)
A novel electrochemical sensor based on a glassy carbon electrode, modified with reduced graphene oxide and copper nanoparticles (GC/rGO-CuNPs), was developed for the determination of glyphosate herbicide (GLY) by differential pulse voltammetry (DPV). The proposed material was synthesised by a chemical method and characterised by scanning electron microscopy (SEM) and cyclic voltammetry (CV). Voltammetric tests showed that the anodic peak at 30 mV, due to the Cu0 to Cu2+ oxidation process, decreased linearly with small additions of GLY; this inhibition was used to quantify the pesticide content in water by DPV. The GC/rGO-CuNPs electrode was evaluated and optimised for the determination of GLY in tap water samples without any pretreatment, achieving a linear response in the range of 0.1 to 1.1 µmol L−1 with a detection limit of 0.19 µmol L−1 (R2 = 0.9996). This study provides a new application for graphene-based sensors and a promising alternative for GLY analysis.
Keywords: copper nanoparticles; electrochemical sensor; Glyphosate; reduced graphene oxide